The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s42825-022-00102-6
|View full text |Cite
|
Sign up to set email alerts
|

Advanced application of collagen-based biomaterials in tissue repair and restoration

Abstract: In tissue engineering, bioactive materials play an important role, providing structural support, cell regulation and establishing a suitable microenvironment to promote tissue regeneration. As the main component of extracellular matrix, collagen is an important natural bioactive material and it has been widely used in scientific research and clinical applications. Collagen is available from a wide range of animal origin, it can be produced by synthesis or through recombinant protein production systems. The use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 143 publications
0
10
0
Order By: Relevance
“…As mentioned in several studies, collagen has poor mechanical properties in regenerative medicine applications 72 , 73 . Compressing collagen constructs is a promising method for improving their mechanical properties in tissue engineering applications.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned in several studies, collagen has poor mechanical properties in regenerative medicine applications 72 , 73 . Compressing collagen constructs is a promising method for improving their mechanical properties in tissue engineering applications.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, bone is a load-bearing organ with certain mechanical strength, and biomaterials with the same Young’s modulus as bone are highly sought after. For repairable bone injuries, biomaterials are generally selected to be biodegradable at a rate comparable to the bone healing cycle ( Borchers and Pieler, 2010 ; Gorejová et al, 2018 ; Zhu et al, 2022 ).…”
Section: Interaction Of Materials and Immune Cellsmentioning
confidence: 99%
“…Although some studies have reported that the addition of collagen to fibrin hydrogels can improve their mechanical properties, there is still room for improvement to achieve optimal stiffness and elasticity for different tissue types. 237 Additionally, some drawbacks have been reported in the application of these types of hydrogels, such as the low mechanical strength and low osteogenicity of collagen, limiting their application in bone regeneration 238 ; thrombogenic properties and in vivocalcification in cardiovascular repair 238 ; and the lack of revascularization in multilayered tissues. 239 The combination of fibrin and alginate has also shown promise in promoting the growth of ovarian follicles and bone tissue regeneration.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%